Is the Care Transitions Measure Associated with Readmission Risk? Analysis from a Single Academic Center - Goldstein, Jennifer N. (J Gen Intern Med, 2016)
BACKGROUND: It is widely hypothesized that improvement in transitions of care will reduce unplanned hospital readmissions. However, the association between the Care Transitions Measure, the national quality metric for transitions of care and readmission risk, has not been established. OBJECTIVE: We aimed to determine the association between the Care Transition Measure and readmission. DESIGN: This was a single-center, prospective cohort study. PARTICIPANTS: Convenience sample of 2,963 patients enrolled in the “Bridging the Divides” program, a longitudinal care management program for patients with coronary revascularization, from 2013 to 2014. Of these, 1594 (54 %) patients completed a post-discharge Care Transition Measure questionnaire. INTERVENTION: Care Transition Measure scores were collected by trained research staff blinded to study hypothesis, by telephone, within 30 days of discharge. Higher Care Transition Measure scores reflect a higher quality transition of care. MAIN MEASURES: 30-day readmission was measured. KEY RESULTS: Of the1594 patients that completed the Care Transition Measure survey, 1216 (76 %) received percutaneous coronary intervention and 378 (24 %) received coronary artery bypass grafting. Mean Care Transition Measure scores were significantly lower among patients who had a prior admission (77.2 vs. 82.1, p < 0.001) and those with ≥ 5 comorbidities (77 vs. 82.6 vs. 81.6, p < 0.001). Mean scores were significantly lower among patients who were readmitted within the percutaneous coronary intervention subgroup (73 vs. 80.9, p < 0.001) and the total study population (74.6 vs. 81.1, p < 0.001) compared to those who were not readmitted. This was not the case in the coronary artery bypass grafting subgroup (78.5 vs. 81.7, p = 0.29). After multivariable adjustment, every ten-point increase in the Care Transition Measure score was associated with a 14 % reduction in readmission risk (adjusted odds ratio 0.86, 95 % CI 0.78–0.95). CONCLUSIONS: The Care Transition Measure is strongly associated with readmissions, which strengthens its validity. However, its association with patient variables linked with readmission and its inconsistent association with readmission across clinical groups raises concerns that scores may be influenced by patient characteristics.